Intersectionality, Sexuality, and Psychological Therapies : Working with Lesbian, Gay, and Bisexual Diversity - Das Nair, Roshan; Butler, Catherine, 1972- (Chichester, West Sussex, UK ; Hoboken : Wiley, 2012)
"This book explores the diversity in lesbian, gay, and bisexual lives, with the aim of opening up therapists' understanding of this diversity so that they can work in an ethical, supportive and non-discriminatory way with these individuals. Offers a comprehensive look at diversity within LGB populations, including the interactions between different areas of social difference using contemporary approaches; Focuses on the practitioner, illustrating concepts with vignettes and case studies for implementing practical applications; Emphasizes gender balance, fully exploring both male and female perspectives on each topic; Encompasses different perspectives, including critical health psychology, discursive psychology, intersectionality, critical and cultural theory, and post-colonial discourse, while remaining accessible to all"--Provided by publisher.
Introduction / Roshan das Nair and Catherine Butler -- Intersecting identities / Damien W. Riggs and Roshan das Nair -- Gender / Sonja J. Ellis -- Race and ethnicity / Roshan das Nair and Sonya Thomas -- Religion / Roshan das Nair and Sonya Thomas -- Refugees and asylum seekers / Stephen Higgins and Catherine Butler -- Social class / Roshan das Nair and Susan Hansen -- Physical health / Adam Jowett and Elizabeth Peel -- Mental health / Roshan das Nair and Sarah Fairbank -- Disability / Catherine Butler -- Age and ageing / Stuart Gibson and Susan Hansen -- From invert to intersectionality : understanding the past and future of sexuality / Esther D. Rothblum.
Includes bibliographical references and index.
Print version record.
Keywords: Gays -- Mental health; Psychoanalysis and homosexuality; Bisexuality; Homosexuality; Psychoanalysis -- methods; Social Class; MEDICAL -- Mental Health; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; PSYCHOLOGY -- Psychopathology -- General; Gays -- Mental health; Psychoanalysis and homosexuality; Electronic books